Sosialisasi Gerakan Memasyarakatkan Makan Ikan (GEMARIKAN) dalam Upaya Mencegah Stunting di Posyandu Kenanga, Kampung Rempak, Kec. Sabak Auh, Kab. Siak - Sesdia Angela; Novi Aulia Wati; Mifta Khairunisa; Anisa Rispa Rahayu; Anisa Salsabila Putri; Ade Kurniawan; Fadila Patricia; Kania Ramadhisa; Najwah Khoirunnisa; Pradita Nemas Ariestya; Rossa Oktavia; Syahroni Aminullah (Yayasan Daarul Huda Kruengmane, 2026)
Stunting is one of the nutritional problems that can hinder children’s growth and development. Therefore, preventive efforts are needed through the fulfillment of balanced nutrition, one of which is by increasing fish consumption as a source of animal protein. This community service activity aimed to provide education on the importance of fish consumption through the GEMARIKAN (Fish-Eating Community Movement) Program at Kenanga Integrated Health Post (Posyandu), Rempak Village, Sabak Auh District, Siak Regency. The methods used included an initial survey, interactive counseling, an introduction to catfish nuggets as an example of a processed fish product, as well as discussions and question-and-answer sessions. The results showed that participants actively and enthusiastically participated in the educational session and gained an understanding of the benefits of fish consumption, its nutritional content, and alternative ways of processing fish that can be incorporated into family meals. The GEMARIKAN Program serves as an educational medium with the potential to increase community awareness of the importance of fish consumption as part of fulfilling balanced nutrition and supporting stunting prevention efforts.